2023
DOI: 10.1111/aec.13326
|View full text |Cite
|
Sign up to set email alerts
|

Speedy blooming in Cerrado after fire is not uncommon: New records of Cyperaceae species flowering 24 h after burning

Abstract: Fire‐stimulated flowering has long been a subject of investigation in tropical grasslands and savannas. Still, speedy blooming (i.e. flowering in <24 h after fire) had only been recently described for a single species of Cyperaceae common in Cerrado open ecosystems. Here, we described two new species displaying this unique feature of producing flowers <24 h after fire, suggesting that this fast phenological response might be more common than previously thought. Rhynchospora confusa F.Ballard and Rhynchospora t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Recent studies have shown that even a small amount of leaf damage may induce a significant increase in flowering [ 54 ], and the removal of the dry leaves (except for the leaf base) also stimulated flowering of B . paraxoda similar to the recently reported for Rhynchospora confusa (Cyperaceae) [ 55 ]. Bulbostylis paradoxa has a shallow root system, and does not have a prostrate architecture suggesting that the species did not evolve under intense grazer pressure [ 56 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recent studies have shown that even a small amount of leaf damage may induce a significant increase in flowering [ 54 ], and the removal of the dry leaves (except for the leaf base) also stimulated flowering of B . paraxoda similar to the recently reported for Rhynchospora confusa (Cyperaceae) [ 55 ]. Bulbostylis paradoxa has a shallow root system, and does not have a prostrate architecture suggesting that the species did not evolve under intense grazer pressure [ 56 ].…”
Section: Discussionsupporting
confidence: 90%
“…Yet, as the fire-stimulated flowering is independent of fire season, the changes in fire regime imposed by anthropogenic fires might significantly impact the benefits of such adaptation. Therefore, we propose that plant damage by fire or another agent might also trigger, in other herbaceous layer species, a multi-response process, as recently reported by Pilon et al [ 55 ] which observed a single individual of R . confusa half-mowed flowering in an unburned area.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation